THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT PT. BANK MANDIRI (PERSERO) TBK. SIDRAP DISTRICT BRANCH - Anastasia D'Ornay; Maskur Hasan (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine and analyze how much influence service quality has on customer satisfaction at PT. Bank Mandiri (Persero) Tbk. Sidrap District Branch. The analytical method used in this study is the method of observation, questionnaires, interviews, and documentation with the method of determining the sample used as many as 378 samples, the analytical method used is multiple linear analysis using SPSS version 20. The results show that the strength of the relationship is simultaneously between reliability ( X1), responsiveness (X2), assurance (X3), empathy (X4), and physical evidence (X5) on customer satisfaction (Y) at PT.Bank Mandiri (Persero) Tbk. Sidrap District Branch obtained the value of r = 0.299. This value shows a very strong positive relationship simultaneously between the variables of reliability, responsiveness, assurance, empathy, and physical evidence on customer satisfaction of PT. Bank Mandiri (Persero) Tbk. Sidrap District Branch. The contribution or determination given by the variables of reliability, responsiveness, assurance, empathy, and physical evidence on customer satisfaction is D = (0.299)2 × 100% = 89%. This means that the five independent variables contribute an influence of 89% on customer satisfaction, 11% is influenced by other variables that affect customer satisfaction not included in the study. The regression equation is as follows: Y = 7.951 + 0.066X1 + 0.210X2 + 0.058X3 + 0.119X4 + 0.107X5 + 1.858. The F test shows Farithmetic Ftable then there is a simultaneous significant effect between reliability, responsiveness, assurance, empathy, and physical evidence on customer satisfaction at PT. Bank Mandiri (Persero) Tbk. Sidrap District Branch.